Improving the quality of paddy and pricing issues through process optimization in a rice company - Nurin Mastura, Afandi; Lee, Khai Loon (Penerbit Universiti Malaysia Pahang, 2023)
This research aims to improve the quality of paddy and address pricing issues through process optimization in APRM. The study focuses on identifying the manufacturing process of paddy, optimizing it to enhance quality, and suggesting procurement practices to resolve pricing issues. The research employed a semi-structured interview approach to collect data. The findings provide valuable recommendations for APRM to optimize the manufacturing process, improve paddy quality, and establish fair pricing structures. The significance of the study lies in its potential to enhance APRM's market competitiveness, improve farmer welfare, promote sustainability, contribute to the agricultural industry's advancement, and influence policy and decision-making. The research concludes with a discussion, highlighting the research's implications, addressing gaps in the literature, and offering recommendations for future research. Implementing the suggested strategies can lead to improved paddy quality, stable pricing, and overall growth for APRM and the agricultural sector. By implementing the suggested strategies, APRM has the opportunity to achieve improved paddy quality, stable pricing, and overall growth, thereby positioning itself as a leading player in the rice industry.